Channelling carbon flux through the meta‐cleavage route for improved poly(3‐hydroxyalkanoate) production from benzoate and lignin‐based aromatics in Pseudomonas putida H. Issue 6 (10th November 2020) - Borrero‐de Acuña, José Manuel; Gutierrez‐Urrutia, Izabook; Hidalgo‐Dumont, Cristian; Aravena‐Carrasco, Carla; Orellana‐Saez, Matias; Palominos‐Gonzalez, Nestor; van Duuren, Jozef B. J. H.; Wagner, Viktoria; Gläser, Lars; Becker, Judith; Kohlstedt, Michael; Zacconi, Flavia C.; et al.
Summary: Lignin‐based aromatics are attractive raw materials to derive medium‐chain length poly(3‐hydroxyalkanoates) ( mcl ‐PHAs), biodegradable polymers of commercial value. So far, this conversion has exclusively used the ortho‐ cleavage route of Pseudomonas putida KT2440, which results in the secretion of toxic intermediates and limited performance. Pseudomonas putida H exhibits the ortho‐ and the meta‐ cleavage pathways where the latter appears promising because it stoichiometrically yields higher levels of acetyl‐CoA. Here, we created a double‐mutant H‐Δ catA Δ A2 that utilizes the meta route exclusively and synthesized 30% more PHA on benzoate than the parental strain but suffered from catechol accumulation. The single deletion of the catA 2 gene in the H strain provoked a slight attenuation on the enzymatic capacity of the ortho route (25%) and activation of the meta route by nearly 8‐fold, producing twice as much mcl ‐PHAs compared to the wild type. Inline, the mutant H‐Δ catA 2 showed a 2‐fold increase in the intracellular malonyl‐CoA abundance – the main precursor for mcl‐ PHAs synthesis. As inferred from flux simulation and enzyme activity assays, the superior performance of H‐Δ catA 2 benefited from reduced flux through the TCA cycle and malic enzyme and diminished by‐product formation. In a benzoate‐based fed‐batch, P . putida H‐Δ catA 2 achieved a PHA titre of 6.1 g l –1 and a volumetric productivity of 1.8 g l –1 day –1 . Using Kraft lignin hydrolysate as feedstock, the engineered strain formed 1.4 g l ‐ 1 PHA. The balancing of carbon flux between the parallel catechol‐degrading routes emerges as an important strategy to prevent intermediate accumulation and elevate mcl‐ PHA production in P. putida H and, as shown here, sets the next level to derive this sustainable biopolymer from lignin hydrolysates and aromatics. Abstract : Engineered P . putida H sets a benchmark in lignin‐based PHA. Balancing the catechol degrading pathways enables improved PHA production. A DO‐stat fed‐batch process permits the efficient conversion of lignin hydrolysates into biomass and biopolymer.